PREDIKSI PEMUTUSAN RANTAI PENYAKIT TALASEMIA DENGAN PERNIKAHAN TERKONTROL MENGGUNAKAN DIAGONALISASI MATRIKS (Universitas Islam Negeri Alauddin Makassar, 2026)
Human diseases can arise from various factors, one of which is heredity. In this case, individuals inherit specific genetic traits from their parents that may lead to disease. Thalassemia is one such hereditary disease. A key preventive measure against thalassemia is avoiding marriages between individuals who both carry the thalassemia gene, whether in the minor or major form. The transmission of thalassemia genes across generations can be modeled using a matrix that represents the probabilities of gene inheritance. This study, conducted through a literature review approach, demonstrates the probabilities of thalassemia gene types in the n-th generation under controlled marriage conditions, where marriage is permitted only if at least one parent is of normal genotype (neither affected nor a carrier). A probability matrix of thalassemia inheritance is constructed, followed by the determination of eigenvalues and eigenvectors for matrix diagonalization. This approach is employed to predict the distribution of genotypes in the n-th generation. The findings indicate that, under controlled marriage conditions, thalassemia major will be completely eliminated by the first generation, thereby preventing its occurrence in subsequent generations. Furthermore, over successive generations, the proportion of thalassemia minor cases will gradually decline and eventually approach zero.